Development of a working core outcome set for cutaneous lupus erythematosus: a practical approach to an urgent unmet need - Victoria P Werth; Joseph F Merola; Vinod E Nambudiri; Robert Borucki; Lisa N Guo; Lourdes M Perez-Chada (Lupus Science and Medicine)
Objective The lack of standardised outcomes and outcome measures for cutaneous lupus erythematosus (CLE) represents a substantial barrier to clinical trial design, comparative analysis and approval of novel investigative treatments. We aimed to develop a working core outcome set (COS) for CLE randomised controlled trials and longitudinal observational studies.Methods We conducted a multistage literature review of CLE and SLE studies to generate candidate domains and outcome measures. Domains were narrowed to a working core domain set. Outcome measures for core domains were identified and examined.Results Proposed core domains include skin-specific disease activity and damage, investigator global assessment (IGA) of disease activity, symptoms (encompassing itch, pain and photosensitivity), health-related quality of life (HRQoL) and patient global assessment (PtGA) of disease activity. Recommended physician-reported outcome measures include the Cutaneous Lupus Erythematous Disease Area and Severity Index (CLASI) and Cutaneous Lupus Activity IGA (CLA-IGA). For the domains of symptoms, HRQoL and PtGA of disease activity, we were unable to recommend one clearly superior instrument.Conclusion This work represents a starting point for further refinement pending formal consensus activities and more rigorous evaluations of outcome measure quality. In the interim, the proposed working COS can serve as a much-needed guide for upcoming CLE clinical trials.